Case Study: The Myanmar and Bangladesh Maritime Boundary Dispute in the Bay of Bengal and Its Implications for South China Sea Claims - Ravi A. Balaram (Journal of Current Southeast Asian Affairs, 2012)
This paper seeks to review the pertinent Myanmar and Bangladesh history in overlapping maritime territorial claims leading up to the September 2011 International Tribunal for the Law of the Sea (ITLOS) case: Dispute Concerning Delimitation of the Maritime Boundary Between Bangladesh and Myanmar in the Bay of Bengal. It will dissect the legal proceedings as primary source documents and apply the relevant judgement findings to analyse the implications for the respective countries and for South China Sea maritime boundary disputes. While the judgements of this case set certain legal precedents that may be more easily applied to bilateral disputes, the implications, nevertheless, impinge on multilateral claims as well. To the extent that the Bangladesh-Myanmar ITLOS judgement provides a pathway to third-party, independent, and peaceful resolution to the potentially explosive and escalating tensions in the South China Sea, this paper argues that findings are relevant, but limited.